Sigmund Schenklings Konvolut und sein ’Faunistischer Führer durch die Coleopteren-Literatur’. - Rohlfien, Klaus (Contributions to Entomology = Beiträge zur Entomologie, 1994)
The archives of the library of the Deutsches Entomologisches Institut (DEI) contain the unpublished and incomplete manuscript of Sigmund Schenkling’s ’Faunistischer Führer durch die Coleoptera-Literatur’. A brief biography is followed by an analysis of his contributions as a collaborator of the DEI, scientist, bibliographer and editor. The structure, form and chronological limits of the manuscript are discussed.